Method and device for compressing and fixing glass fiber diaphragm of water-based battery

By injecting electrolyte with glass fiber diaphragm and applying pressure during the lead-acid separator battery manufacturing process, the problems of large cell thickness and poor fixed position are solved, the solid shape and stable shape of the cell are realized, and the production efficiency and battery are improved. performance.

CN119208769APending Publication Date: 2024-12-27ZHEJIANG VASTECH ENERGY CO LTD

Patent Information

Application Number
CN202411715374.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

During the manufacturing process of lead-acid diaphragm batteries, the large thickness of the battery cell leads to unfavorable space occupation and performance, and the position of the electrode plate and the diaphragm is poor, affecting the quality and performance of the battery cell, resulting in difficulty in entering the battery cell, and seriously hindering the improvement of production efficiency.

Method used

The compression and solidification method of glass fiber diaphragm of water-based battery is adopted. By injecting electrolyte into the glass fiber diaphragm, a preliminary adsorption layer is formed, and the electrolyte is filled and air is extruded in the film, so as to achieve the overall liquid moisture of the glass fiber diaphragm and the battery core. Solid shape ensures that the battery cell maintains a stable shape during subsequent use and processing.

Benefits of technology

Effectively reduce the thickness of the battery cell, improve the electrolyte injection and emulsion efficiency, ensure the smooth entry of the battery cell into the shell, improve the efficiency of the production process, enhance the stability and cycle life of the battery, prevent the short circuit of the positive and negative electrodes, and optimize the charging. Volume changes during discharge reduce performance decay caused by mechanical stress.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208769A_ABST
    Figure CN119208769A_ABST
Patent Text Reader

Abstract

The invention discloses a method and a device for compressing and fixing a glass fiber diaphragm of an aqueous battery. The method comprises the following steps: providing a positive plate, a negative plate and a glass fiber diaphragm; placing a glass fiber diaphragm between the positive plate and the negative plate for lamination to form a battery cell, and in the lamination process, injecting a certain amount of electrolyte into the film surface of the glass fiber diaphragm to moisten the glass fiber diaphragm so as to primarily adsorb the positive plate and the negative plate; and applying balanced pressure to the battery cell, so that the electrolyte is filled in the glass fiber diaphragm and air in the diaphragm is extruded, the glass fiber diaphragm is wholly moistened and fully adsorbs the positive plate and the negative plate, and the battery cell is compressed and shaped under the balanced pressure. A certain amount of electrolyte is injected into each glass fiber diaphragm, and the electrolyte forms a preliminary adsorption layer to realize adsorption of the positive plate and the negative plate; and by applying balanced pressure, the whole glass fiber diaphragm is moistened by liquid, and the shape fixing of the battery cell is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery manufacturing, and more specifically, to a method and device for compressing and solidifying a glass fiber diaphragm of an aqueous battery. Background Art

[0002] At present, the manufacturing process of lead-acid diaphragm batteries is usually as follows: positive electrode sheets, diaphragms, and negative electrode sheets are stacked to form a battery cell, and then tape is affixed to the outer surface of the battery cell to fix it, and then the fixed battery cell is packaged.

[0003] However, in the manufacturing process of lead-acid diaphragm batteries, there are the following problems:

[0004] 1. The thickness of the battery cell is relatively large, which not only takes up too much space, but also has an adverse effect on the overall energy density and other performance of the battery;

[0005] 2. During the battery cell assembly process, the position between the pole piece and the diaphragm cannot be effectively fixed. This unfixed position makes it easy for the pole piece and the diaphragm to be misaligned during the assembly process, further affecting the quality and performance of the battery cell;

[0006] What is more serious is that due to the existence of the above-mentioned problems, after the battery cells are assembled, the battery cells often cannot be smoothly inserted into the square shell. A lot of time and manpower are needed to adjust and correct them to deal with the problems of large battery cell thickness and difficulty in inserting the battery cells into the shell, which seriously hinders the improvement of production efficiency and the normal production of battery products.

[0007] Therefore, it is necessary to propose a new solution to solve the above problems. Summary of the invention

[0008] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and to provide a method and device for compressing and solidifying glass fiber diaphragms of aqueous batteries. During the process of stacking battery cells, a certain amount of electrolyte is injected into each glass fiber diaphragm to moisten the glass fiber diaphragm. The electrolyte forms a preliminary adsorption layer on the surface of the glass fiber diaphragm by the force between liquid molecules to achieve adsorption of the positive and negative electrodes. At the same time, a balanced pressure is applied to the battery cell with the preliminary adsorption layer, so that the electrolyte fills the glass fiber diaphragm and squeezes out the air in the membrane, thereby achieving liquid infiltration of the entire glass fiber diaphragm, forming an overall liquid adsorption layer to achieve solidification of the battery cell, and effectively ensuring that the battery cell maintains a stable shape during subsequent use and processing.

[0009] In order to achieve the above object, the present invention adopts the following technical solution:

[0010] A method for compressing and solidifying a glass fiber diaphragm of an aqueous battery, comprising the following steps:

[0011] Step 1, providing a positive electrode sheet, a negative electrode sheet, and a glass fiber separator;

[0012] Step 2, placing a glass fiber separator between a positive electrode sheet and a negative electrode sheet to form a battery core, and during the lamination process, injecting a certain amount of electrolyte into the membrane surface of the glass fiber separator to wet the glass fiber separator, and the wetted glass fiber separator initially absorbs the positive electrode sheet and the negative electrode sheet;

[0013] Step 3, applying balanced pressure to the battery cell, so that the electrolyte fills the glass fiber diaphragm and squeezes out the air in the membrane, so that the glass fiber diaphragm is completely moistened, and the overall moistened glass fiber diaphragm fully absorbs the positive electrode sheet and the negative electrode sheet, and under balanced pressure, the battery cell is compressed and solidified.

[0014] Preferably, in step 2, the battery cell stacks are arranged in a cycle in the order of a glass fiber diaphragm, a positive electrode sheet, a glass fiber diaphragm, and a negative electrode sheet, and the electrolyte is injected into the membrane surface on one side of the glass fiber diaphragm in a matrix form, and the positive electrode sheet and the negative electrode sheet are adsorbed on the glass fiber diaphragm through the electrolyte.

[0015] The present invention also provides a water-based battery glass fiber diaphragm compression solidification device, comprising:

[0016] A diaphragm conveying mechanism, used for conveying a glass fiber diaphragm;

[0017] A lamination platform for fixing the glass fiber separator to laminate the positive and negative electrode sheets;

[0018] A glass fiber diaphragm positioning platform is used to position the glass fiber diaphragm and place the glass fiber diaphragm on the stacking platform;

[0019] A positive electrode sheet positioning platform is provided on one side of the stacking platform and is used to position the positive electrode sheet so as to place the positive electrode sheet on the glass fiber diaphragm from one side of the glass fiber diaphragm;

[0020] A negative electrode sheet positioning platform is provided on the other side of the stacking platform and is used to position the negative electrode sheet so as to place the negative electrode sheet on the glass fiber separator from one side of the glass fiber separator;

[0021] The liquid injection head is arranged above the lamination platform and is used to inject electrolyte into the glass fiber diaphragm during the lamination process, so that after the positive electrode sheet is placed, the positive electrode sheet is adsorbed on one side of the glass fiber diaphragm through the electrolyte, and after the negative electrode sheet is placed, the negative electrode sheet is adsorbed on one side of the glass fiber diaphragm through the electrolyte;

[0022] The pressure plate is used to evenly apply the pressure output by the pressure mechanism to the battery cell, so that the injected electrolyte fills the glass fiber diaphragm and squeezes out the air in the membrane, thereby achieving overall wetting of the glass fiber diaphragm. The overall wetting of the glass fiber diaphragm fully absorbs the positive electrode sheet and the negative electrode sheet, and the battery cell is compressed and solidified under balanced pressure.

[0023] The beneficial effects of the present invention are:

[0024] 1. In the present invention, during the process of stacking battery cells, a certain amount of electrolyte is injected into each glass fiber diaphragm to infiltrate the glass fiber diaphragm. The electrolyte forms a preliminary adsorption layer on the surface of the glass fiber diaphragm by the force between liquid molecules, so as to achieve adsorption of the positive electrode sheet and the negative electrode sheet. At the same time, a balanced pressure is applied to the battery cell with the preliminary adsorption layer formed, so that the electrolyte fills the glass fiber diaphragm to squeeze out the air in the membrane, so as to achieve liquid infiltration of the entire glass fiber diaphragm, form an overall liquid adsorption layer to achieve solidification of the battery cell, and effectively ensure that the battery cell maintains a stable shape during subsequent use and processing.

[0025] 2. In the present invention, the glass fiber diaphragm is pressurized so that the electrolyte can penetrate the whole body and discharge the internal air, so that in the subsequent electrolyte injection process, the injection and wetting efficiency of the electrolyte is improved and the static time is reduced; at the same time, the glass fiber diaphragm is pressurized so that the air contained therein is effectively discharged, so that the thickness of the glass fiber diaphragm is compressed, thereby facilitating the smooth insertion of the battery cell into the shell, reducing unnecessary pauses and interventions, and improving the effect of the entire production process.

[0026] 3. The present invention helps maintain the internal stability of the battery, prevents short circuits between the positive and negative electrodes, and improves the cycle life and safety of the battery by controlling the thickness of the glass fiber diaphragm and the fixed shape of the battery cell; at the same time, the optimized glass fiber diaphragm can better adapt to volume changes during charging and discharging, reduce battery performance degradation caused by mechanical stress, and enable the battery to maintain stable performance output during long-term use. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of a use of a cell stack of a glass fiber diaphragm compression solidification device for an aqueous battery in this embodiment;

[0028] Figure 2 It is a schematic diagram of the use of the glass fiber diaphragm compression and solidification device for aqueous batteries in this embodiment to compress and solidify the battery cells.

[0029] Figure numerals: positive electrode sheet 1, negative electrode sheet 2, glass fiber diaphragm 3, electrolyte 4, glass fiber diaphragm positioning platform 5, stacking platform 6, injection head 7, positive electrode sheet positioning platform 8, negative electrode sheet positioning platform 9, pressing plate 10, carrying platform 11, pressure cylinder 12. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Embodiment: A method for compressing and solidifying a glass fiber diaphragm of an aqueous battery, comprising the following steps:

[0032] Step 1, providing a die-cut positive electrode sheet 1 and a negative electrode sheet 2, and a glass fiber separator 3;

[0033] Step 2, placing the glass fiber separator 3 between the positive electrode sheet 1 and the negative electrode sheet 2 to form a battery core, and during the lamination process, injecting a certain amount of electrolyte 4 into the membrane surface of the glass fiber separator 3 to wet the glass fiber separator 3, and the wetted glass fiber separator 3 initially absorbs the positive electrode sheet 1 and the negative electrode sheet 2;

[0034] Step 3, applying balanced pressure to the battery cell, so that the electrolyte 4 fills the glass fiber diaphragm 3 and squeezes out the air in the membrane, so that the glass fiber diaphragm 3 is completely moistened, and the completely moistened glass fiber diaphragm 3 fully absorbs the positive electrode sheet 1 and the negative electrode sheet 2, and the battery cell is compressed and solidified under balanced pressure.

[0035] Wherein, step 2 specifically includes:

[0036] The battery cell stack is arranged in a cycle in the order of a glass fiber separator 3, a positive electrode sheet 1, a glass fiber separator 3, and a negative electrode sheet 2. The electrolyte 4 is injected into the membrane surface on one side of the glass fiber separator 3 in a matrix form, and the positive electrode sheet 1 and the negative electrode sheet 2 are adsorbed on the glass fiber separator 3 through the electrolyte 4.

[0037] During the battery cell stacking process, a certain amount of electrolyte 4 is injected into each glass fiber diaphragm 3 to infiltrate the glass fiber diaphragm 3. The electrolyte 4 molecules are guided by the surface force field to form a preliminary adsorption layer to achieve adsorption of the positive electrode sheet 1 and the negative electrode sheet 2. At the same time, a balanced pressure is applied to the battery cell that forms the preliminary adsorption layer, so that the electrolyte 4 fills the glass fiber diaphragm 3 to squeeze out the air in the membrane, so that the entire glass fiber diaphragm 3 is infiltrated with liquid, and an overall liquid adsorption layer is formed to achieve the solidification of the battery cell. Among them, the glass fiber diaphragm 3 has a large porosity, and the air contained therein can be effectively removed by compression, and the thickness of the glass fiber diaphragm 3 is compressed. The size of the glass fiber diaphragm 3 is slightly larger than the positive electrode sheet 1 and the negative electrode sheet 2, so as to achieve the effect of completely covering the positive electrode sheet 1 and the negative electrode sheet 2.

[0038] After the battery cell is solidified, the glass fiber separator 3 has its internal air discharged and is infiltrated with the electrolyte 4, so that in the subsequent electrolyte 4 injection process, the injection and infiltration efficiency of the electrolyte 4 is improved and the static time is reduced; at the same time, the glass fiber separator 3 absorbs the positive electrode sheet 1 and the negative electrode sheet 2 through the infiltrated electrolyte 4, so that the positive electrode sheet 1 and the negative electrode sheet 2 are in a fixed state, and the shape of the battery cell is fixed, thereby ensuring that the battery cell maintains a stable shape during subsequent use and processing.

[0039] like Figure 1 , Figure 2 As shown, the present invention also provides a glass fiber diaphragm compression and solidification device for an aqueous battery, comprising a lamination platform 6, a liquid injection head 7, a positive electrode sheet positioning platform 8, a negative electrode sheet positioning platform 9, a pressing plate 10 and a glass fiber diaphragm positioning platform 5;

[0040] Among them, the stacking platform 6 is used to fix the glass fiber diaphragm 3 to stack the positive electrode sheet 1 and the negative electrode sheet 2; the glass fiber diaphragm positioning platform 5 is used to position the glass fiber diaphragm 3 and place the glass fiber diaphragm 3 on the stacking platform 6; the positive electrode sheet positioning platform 8 is arranged on one side of the stacking platform 6, and is used to position the positive electrode sheet 1, so as to place the positive electrode sheet 1 on the glass fiber diaphragm 3 from one side of the glass fiber diaphragm 3; the negative electrode sheet positioning platform 9 is arranged on the other side of the stacking platform 6, and is used to position the negative electrode sheet 2, so as to place the negative electrode sheet 2 on the glass fiber diaphragm 3 from one side of the glass fiber diaphragm 3; the injection head 7 is arranged above the stacking platform 6 , used to inject electrolyte 4 into the glass fiber diaphragm 3 during the lamination process, so that after the positive electrode sheet 1 is placed, the positive electrode sheet 1 is adsorbed on one side of the glass fiber diaphragm 3 through the electrolyte 4, so that after the negative electrode sheet 2 is placed, the negative electrode sheet 2 is adsorbed on the other side of the glass fiber diaphragm 3 through the electrolyte 4; the pressing plate 10 is used to evenly apply the pressure output by the pressure mechanism to the battery cell, so that the injected electrolyte 4 fills the glass fiber diaphragm 3 and squeezes out the air in the membrane, so that the entire glass fiber diaphragm 3 is infiltrated with the electrolyte 4, and the overall infiltrated glass fiber diaphragm 3 fully adsorbs the positive electrode sheet 1 and the negative electrode sheet 2, and the battery cell is compressed and solidified under the balanced pressure.

[0041] When stacking the battery cells, the injection head 7 injects a certain amount of electrolyte 4 in a matrix into the membrane surface on one side of the glass fiber diaphragm 3 on the stacking platform 6, and then the positive electrode sheet 1 is sucked from the positive electrode sheet positioning platform 8 and placed on the glass fiber diaphragm 3, and the positive electrode sheet 1 is adsorbed on one side of the glass fiber diaphragm 3 through the electrolyte 4, and then the glass fiber diaphragm 3 is sucked from the glass fiber diaphragm positioning platform 5 to cover the positive electrode sheet 1, and the injection head 7 injects a certain amount of electrolyte 4 in a matrix into the membrane surface on one side of the glass fiber diaphragm 3, and then the negative electrode sheet 2 is sucked from the negative electrode sheet positioning platform 9 and placed on the glass fiber diaphragm 3, and the negative electrode sheet 2 is adsorbed on one side of the glass fiber diaphragm 3 through the electrolyte 4, and thus a battery cell is formed by cyclically arranging a piece of glass fiber diaphragm 3, a piece of positive electrode sheet 1, a piece of glass fiber diaphragm 3, and a piece of negative electrode sheet 2 in this order.

[0042] Furthermore, the battery cell is transferred to the pressure mechanism, which includes a carrying platform 11, a pressure cylinder 12 and a pressure plate 10; wherein the carrying platform 11 is used to fix the battery cell, and the pressure cylinder 12 is used to output pressure; the pressure plate 10 is connected to the pressure cylinder 12, and the size of the pressure surface of the pressure plate 10 is larger than the size of the battery cell, so that the pressure output by the pressure cylinder 12 is evenly applied to the battery cell. After the battery cell is pressurized, the electrolyte 4 fills the glass fiber diaphragm 3 to squeeze out the air in the membrane, so that the entire glass fiber diaphragm 3 is infiltrated with liquid, forming an overall liquid adsorption layer to achieve the solidification of the battery cell. After the battery cell is solidified, the glass fiber separator 3 has its internal air discharged and is infiltrated with the electrolyte 4, so that in the subsequent electrolyte 4 injection process, the injection and infiltration efficiency of the electrolyte 4 is improved and the static time is reduced; at the same time, the glass fiber separator 3 absorbs the positive electrode sheet 1 and the negative electrode sheet 2 through the infiltrated electrolyte 4, so that the positive electrode sheet 1 and the negative electrode sheet 2 are in a fixed state, and the shape of the battery cell is fixed, thereby ensuring that the battery cell maintains a stable shape during subsequent use and processing.

[0043] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A method for compressing and solidifying a glass fiber diaphragm for an aqueous battery, characterized in that: The steps include: Step 1, providing a positive electrode sheet (1), a negative electrode sheet (2), and a glass fiber separator (3); Step 2, placing a glass fiber separator (3) between the positive electrode sheet (1) and the negative electrode sheet (2) to stack the sheets to form a battery core, and during the stacking process, injecting a certain amount of electrolyte (4) into the membrane surface of the glass fiber separator (3) to wet the glass fiber separator (3), and the wetted glass fiber separator (3) initially absorbs the positive electrode sheet (1) and the negative electrode sheet (2); Step 3, applying a balanced pressure to the battery cell, so that the electrolyte (4) fills the glass fiber diaphragm (3) and squeezes out the air in the membrane, so that the glass fiber diaphragm (3) is completely moistened, and the completely moistened glass fiber diaphragm (3) fully absorbs the positive electrode sheet (1) and the negative electrode sheet (2), and the battery cell is compressed and solidified under the balanced pressure.

2. The method for compressing and solidifying a glass fiber diaphragm for an aqueous battery according to claim 1, characterized in that: In step 2, the battery cell stack is arranged in a cycle in the order of a glass fiber separator (3), a positive electrode sheet (1), a glass fiber separator (3), and a negative electrode sheet (2). The electrolyte (4) is injected into the membrane surface on one side of the glass fiber separator (3) in a matrix form, and the positive electrode sheet (1) and the negative electrode sheet (2) are adsorbed on the glass fiber separator (3) through the electrolyte (4).

3. A compression solidification device for glass fiber diaphragm of water-based battery, characterized in that: include: A lamination platform (6) for fixing the glass fiber separator (3) to laminate the positive electrode sheet (1) and the negative electrode sheet (2); A glass fiber diaphragm positioning platform (5) is used to position the glass fiber diaphragm (3) and place the glass fiber diaphragm (3) on the lamination platform (6); A positive electrode sheet positioning platform (8) is arranged on one side of the stacking platform (6) and is used to position the positive electrode sheet (1) so as to place the positive electrode sheet (1) on the glass fiber separator (3) from one side of the glass fiber separator (3); A negative electrode sheet positioning platform (9) is arranged on the other side of the lamination platform (6) and is used to position the negative electrode sheet (2) so as to place the negative electrode sheet (2) on the glass fiber separator (3) from one side of the glass fiber separator (3); The liquid injection head (7) is arranged above the lamination platform (6) and is used to inject the electrolyte (4) into the glass fiber separator (3) during the lamination process, so that after the positive electrode sheet (1) is placed, the positive electrode sheet (1) is adsorbed on one side of the glass fiber separator (3) through the electrolyte (4), and after the negative electrode sheet (2) is placed, the negative electrode sheet (2) is adsorbed on one side of the glass fiber separator (3) through the electrolyte (4); The pressure plate (10) is used to evenly apply the pressure output by the pressure mechanism to the battery cell, so that the injected electrolyte (4) fills the glass fiber diaphragm (3) and squeezes out the air in the membrane, so that the glass fiber diaphragm (3) is fully moistened. The overall moistened glass fiber diaphragm (3) fully absorbs the positive electrode sheet (1) and the negative electrode sheet (2), and the battery cell is compressed and solidified under the balanced pressure.

Citation Information

Patent Citations

  • Rapid lamination method and lamination tool of battery cell pole group and battery cell pole group

    CN111430774A

  • Battery cell manufacturing method and lithium battery manufacturing method

    CN115411345A

  • Lithium battery pole piece-diaphragm composite lamination device and process

    CN116759658A

  • High-performance battery and manufacturing method thereof

    CN117039179A

  • Lithium ion battery collection is convoluteed and priming device

    CN207719348U

Cited By

  • Lamination process, battery cell and battery

    CN121905920A